The implementation for natural science online lecture with chemistry education base at Nurul Fadhillah school Bandar Setia - Zainuddin Muchtar; Sri Adelila Sari; Siti Rahmah; Moondra Zubir; Rini Selly; Marini Damanik (Jurnal Pendidikan Kimia (JPKim), 2021)
The Covid-19 pandemic forces learning activities to change from classroom learning to online-based learning. Based on the results of the interview, it was found that the teachers at Nurul Fadhilah school did not yet have the readiness to manage online teaching and learning activities, especially in science subjects. The influencing factors are (1) understanding of basic science concepts (physics, chemistry, biology), (2) understanding of systematic online learning management and (3) mastery of Learning Management System (LMS) technology. Therefore, the aim of this activity is to implement LMS technology in the management of online science learning using a basic conceptual approach to chemistry education. LMS is a technology application developed specifically for managing classrooms, distributing learning materials and enabling collaboration between students and teachers online. The LMS used in this activity is Google Classroom. Based on the data, it is known that 65% of the teachers at Nurul Fadhilah School have not managed online science teaching and learning activities using LMS technology. The results of the systematic online science learning management workshop using the basic concepts of chemistry education and the implementation of LMS technology, especially Google Classroom, showed an increase, as many as 80% of teachers have created, designed and managed classes interactively using Google Classroom LMS technology and have integrated the concept of basic chemistry education in science learning. So that students are more happy and comfortable in learning online and are more disciplined in collecting assignments and teachers are more comfortable in managing and evaluating student assignments.Keywords: Natural science, Learning management system, Google classroom